SAT-479 Atypical Presentation of Recurrent Cardiac Tamponade Following Pericardial Window in the Setting of Uncontrolled Hypothyroidism - Khan, Sara Atiq (J Endocr Soc, 2020)
INTRODUCTION: Classically, cardiac tamponade presents with hypotension, distant heart sounds and tachycardia (Beck’s triad). Pericardial window is considered effective treatment. Pericardial effusions are relatively common in hypothyroidism (3-6%) (1). Cardiac tamponade, however, is rarely seen in patients with hypothyroidism secondary to pericardial distensibility and the slow accumulation of fluid, allowing significant fluid accumulation without hemodynamic compromise (2). CLINICAL CASE: A 84 year-old female with history of post-surgical hypothyroidism (on levothyroxine 150 mcg) following total thyroidectomy for thyroid cancer, cardiac tamponade requiring pericardial window formation two years prior, presented for dyspnea on exertion and pedal edema for several days. She was tachypneic to 22/min with heart rate 47/min and blood pressure 92/62. Distant heart sounds were noted on exam. EKG demonstrated sinus bradycardia, low voltage QRS and T wave flattening. Further workup revealed TSH elevated to 44 uIU/mL (N:0.27–4.2 uIU/mL), free T4 0.17 ng/dl (N:0.93-1.7 ng/dl) and undetectable T3 (N: 80-100 ng/dl). Echocardiogram unexpectedly demonstrated a large circumferential pericardial effusion with diastolic collapse of the right atrial, right ventricular free wall, significant respiratory variations and interventricular dependence. These findings were consistent with cardiac tamponade physiology. She underwent a video assisted left thoracotomy pericardial window formation along with drainage of 400cc of yellow pericardial fluid. Fluid cytology and tissue histopathology were negative for malignancy. Her uncontrolled hypothyroidism was considered the cause for recurrence of cardiac tamponade and her levothyroxine dose was increased to 175 mcg. At two week follow up, she reported symptomatic improvement on the higher levothyroxine dose. Echocardiogram did not show reaccumulation of fluid. CONCLUSIONS: Sinus tachycardia is found in most patients with cardiac tamponade, except in hypothyroid patients (2). A high degree of suspicion is needed to diagnose cardiac tamponade in hypothyroidism, even in patients who have undergone presumed definitive therapy with a pericardial window in the past. The recent onset of pedal edema and low blood pressure were important indicators of impending cardiac compromise in our patient. Hypothyroid patients may be at higher risk of pericardial window failure compared to patients with cardiac tamponade of other etiologies, especially if thyroid replacement therapy is inadequate. The scientific literature is lacking in this regard and warrants further investigation. References: 1 Bajaj R, et al. Cardiac tamponade in hypothyroidism. BMJ Case Rep. 2014;:bcr2014204076 2 Wang JL, et al. Hypothyroid cardiac tamponade: clinical features, electrocardiography, pericardial fluid and management. Am J Med Sci 2010;340:276–81.